Labor Market Returns to Early Childhood Stimulation : A 20-year Followup to an Experimental Intervention in Jamaica - Gertler, Paul; Heckman, James; Pinto, Rodrigo; Zanolini, Arianna; Vermeersch, Christel; Walker, Susan; Chang-Lopez, Susan; Grantham-McGregor, Sally (World Bank, Washington, DC, 2013)
This paper finds large effects on the earnings of participants from a randomized intervention that gave psychosocial stimulation to stunted Jamaican toddlers living in poverty. The intervention consisted of one-hour weekly visits from community Jamaican health workers over a 2-year period that taught parenting skills and encouraged mothers to interact and play with their children in ways that would develop their children's cognitive and personality skills. The authors re-interviewed the study participants 20 years after the intervention. Stimulation increased the average earnings of participants by 42 percent. Treatment group earnings caught up to the earnings of a matched non-stunted comparison group. These findings show that psychosocial stimulation early in childhood in disadvantaged settings can have substantial effects on labor market outcomes and reduce later life inequality.